USING PEDAGOGICAL METHODS TO DEVELOP THE SOCIAL CULTURE OF FUTURE RUSSIAN LANGUAGE TEACHERS - Usmanova Munisa Shukhrat qizi (The Conference Hub, 2025)
This article analyses the methods of using pedagogical methods to develop the social culture of future russian language teachers. The pedagogical aspects of developing the social competences of russian language teachers are disclosed.
Keywords: Pedagogy, russian language, teacher, student social competence, methods.